Correction: The effect of ligand, solvent and Cu(0) source on the efficient polymerization of polyether acrylates and methacrylates in aqueous and organic media. Issue 47 (28th November 2017) - Simula, Alexandre; Nikolaou, Vasiliki; Alsubaie, Fehaid; Anastasaki, Athina; Haddleton, David M.
Abstract : Correction for 'The effect of ligand, solvent and Cu(0) source on the efficient polymerization of polyether acrylates and methacrylates in aqueous and organic media' by Alexandre Simula et al., Polym. Chem., 2015, 6, 5940–5950.